2019
DOI: 10.7150/jca.35204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postoperative Radiotherapy in Early Breast Cancer Patients Older than 75 Years: A Propensity-Matched Analysis

Abstract: Background: Currently, there is still some controversy regarding whether early breast cancer patients with a tumor size of ≤5 cm and 1-3 positive lymph nodes should undergo postoperative radiotherapy (PRT). Materials and Methods: We obtained data from the Surveillance, Epidemiology, and End Results (SEER) 18 database. Then, we conducted propensity score matching (PSM), according to the radiotherapy record. The Kaplan-Meier and Cox regression analysis were conducted to explore prognostic factors in breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…In accordance with our findings, Patel et al investigated the role of PMRT in the treatment of patients with T1-T2, N1mic disease, and their results showed that PMRT does not affect the survival of breast cancer patients with N1mic disease, even though elderly patients only accounted for a small portion of the population (with 16% of patients being 65 years or older) [ 18 ]. Contrasting our study, a previous study published by Zhou et al found that PMRT could improve OS for patients aged 75 + years old with a tumor size of ≤ 5 cm and 1–3 positive lymph nodes [ 19 ]. Whereas it is a pity that the population in that study consisted of earlier diagnosed patients (between 1998 and 2005), and the missing data of chemotherapy therapy also could affect the reliability of this study’s results.…”
Section: Discussioncontrasting
confidence: 99%
“…In accordance with our findings, Patel et al investigated the role of PMRT in the treatment of patients with T1-T2, N1mic disease, and their results showed that PMRT does not affect the survival of breast cancer patients with N1mic disease, even though elderly patients only accounted for a small portion of the population (with 16% of patients being 65 years or older) [ 18 ]. Contrasting our study, a previous study published by Zhou et al found that PMRT could improve OS for patients aged 75 + years old with a tumor size of ≤ 5 cm and 1–3 positive lymph nodes [ 19 ]. Whereas it is a pity that the population in that study consisted of earlier diagnosed patients (between 1998 and 2005), and the missing data of chemotherapy therapy also could affect the reliability of this study’s results.…”
Section: Discussioncontrasting
confidence: 99%
“…According to the difference in linear energy transfer (LET), rays are further divided into High-LET and Low-LET clinically. High-energy radiation can directly destroy the single or double strands of DNA in tumor cells, directly leading to the death of tumor cells, whereas low-energy radiation can indirectly cause the death of tumor cells through the generation of oxygen free radicals in cells through ionizing radiation and is affected by the oxygenation of tumor cells, the apoptosis ability of tumor cells, and the cycle of tumor cells ( 49 , 50 ). Therefore, the DNA damage repair ability of tumor cells, the distribution of cell cycle, and the apoptosis pathway of cells are all factors that lead to tumor radiotherapy resistance, and HDACs are involved in these processes to varying degrees.…”
Section: Hdacs and Radiotherapy Resistancementioning
confidence: 99%
“…[ 6 ] For early-stage patients treated with breast-conserving surgery, radiotherapy could decreases local recurrence rates; in node-positive individuals who have undergone mastectomy, radiotherapy improves cancer-specific survival. [ 7 ] Recently, partial breast radiotherapy is increasingly acceptable in early-stage patients treated with breast-conserving surgery, and this strategy needs to be evaluated in the long-term clinical outcomes. [ 8 ] Currently, whole breast irradiation remains the gold standard for early-stage breast cancer patients after breast-conserving surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Radiotherapy has demonstrated efficacy in patients with operable breast cancer, and it is associated with improved treatment outcomes [6] . For early-stage patients treated with breast-conserving surgery, radiotherapy could decreases local recurrence rates; in node-positive individuals who have undergone mastectomy, radiotherapy improves cancer-specific survival [7] . Recently, partial breast radiotherapy is increasingly acceptable in early-stage patients treated with breast-conserving surgery, and this strategy needs to be evaluated in the long-term clinical outcomes [8] .…”
Section: Introductionmentioning
confidence: 99%